High strength steel strip or sheet and method of making the same

CN120858187BActive Publication Date: 2026-10-20VOESTALPINE STAHL GMBH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202480020751.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-03-24
Filing Date
2024-03-22
Publication Date
2026-10-20
Estimated Expiration
2044-03-22

AI Technical Summary

Technical Problem

然而,这样的部件不能由常规的高强度钢生产,因为对于复杂结构部件的可成形性太低

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120858187B_ABST
    Figure CN120858187B_ABST
Patent Text Reader

Abstract

The invention relates to a high strength steel strip or sheet comprising in wt.%: 0.1-0.2 C, 0.3-0.9 Si, 1.4-3.0 Mn, 0.03-1.0 Al, 0.5-1.5 Si+Al. The strip or sheet has a tensile strength (TS) of 780-980 MPa, a microstructure comprising 5-25 vol% of retained austenite. The retained austenite satisfies: a mechanical stability (MS) of 10-35, a retained austenite carbon content of 0.7-1.0, and ≥200. The invention also relates to a method for producing the strip or sheet comprising a double annealing cycle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to high-strength steel strips or sheets suitable for automotive applications. In particular, this invention relates to cold-rolled steel strips or sheets produced by a process involving double annealing of cold-rolled strip. Background Technology

[0002] For a wide variety of applications, increased strength levels are a prerequisite for lightweight structures in the automotive industry, as reduced vehicle weight leads to reduced fuel consumption.

[0003] Automotive body components are often stamped from sheet steel to form complex structural members from thin sheets. However, such components cannot be produced from conventional high-strength steel due to its low formability for complex structures. For this reason, multiphase transformation-induced plasticity assisted steel (TRIP steel) has gained considerable interest in recent years, particularly for applications in automotive body structural components.

[0004] TRIP steel possesses a multiphase microstructure comprising a metastable retained austenite phase capable of generating the TRIP effect. When the steel is deformed, the austenite transforms into martensite, leading to significant work hardening. This hardening effect serves to resist necking in the material and delay failure during sheet forming operations. The microstructure of TRIP steel can significantly alter its mechanical properties.

[0005] Quenching and Partitioning (Q&P) is an annealing cycle consisting of quenching and partitioning steps. In the quenching step, fully austenitized steel or intercritically annealed steel is quenched to the martensite start temperature M0. S and martensite finish temperature M F The temperature is adjusted to achieve partial martensitic transformation. The quenched steel is then held at a temperature equal to or higher than the initial quenching temperature. Austenite (which is dominant after quenching) is stabilized by carbon partitioning from martensite into austenite during partitioning.

[0006] TRIP-assisted steel sheets with an annealed martensitic matrix can be produced by double annealing of cold-rolled strip. The martensitic microstructure after the second annealing step results in a predominantly layered structure, and these steels have a large amount of plate-like retained austenite along the lath boundary of the annealed martensite. Due to the layered structure of the austenite, the stability of the retained austenite in these steels is generally high. The high stability of the retained austenite improves the TRIP effect and overall ductility. The uniform layered structure of the austenite is beneficial for localized ductility.

[0007] US2016 / 0177414A1 discloses a cold-rolled steel that undergoes two annealing processes. After the first annealing, the steel is cooled to 320-500°C and held at 320-500°C for 30 seconds or longer. After the second annealing, the steel is cooled to 120-320°C and subsequently held at 320-500°C for 30 seconds or longer. The steel has a microstructure comprising 3-20% ferrite, 5-20% retained austenite, 5-20% martensite, and the balance being bainite and / or tempered martensite.

[0008] US2017 / 0327924A1 discloses a cold-rolled steel that undergoes two annealing processes. After the first annealing, the steel is cooled to room temperature or a controlled temperature above room temperature, preferably below the martensitic finish temperature, to achieve a predominantly martensitic structure. The second annealing involves soaking within an intercritical range of 720 to 850°C and subsequently holding at 370 to 430°C. The steel has a microstructure consisting of: predominantly austenite (50 to 80% or higher); 5-25% retained austenite; and 0-15% nascent martensite.

[0009] US2020 / 0392598A1, US2020 / 392610A1, US2020 / 00440421A1, US2019 / 203316A1, JP2004238679A2, WO2022 / 123289A1, US2020 / 354823A1, and US2021 / 207236A1 are further examples of annealing that have been proposed multiple times.

[0010] The purpose of this invention is to further improve the steel properties of double annealed steel (preferably, properties related to local and / or overall ductility). Summary of the Invention

[0011] This invention relates to steel strips or sheets with a tensile strength of 780-1350 MPa. The steel strips or sheets are produced in a double annealing process, wherein the first annealing cycle includes quenching to a temperature of M... S -20 and M F The temperature is between [temperature range] and the fractionation occurs at a temperature above the quenching temperature. The second annealing cycle includes quenching to a temperature in the range of 150-500°C and fractionation occurring at a temperature above the quenching temperature or isothermally. The properties of the retained austenite result in improved local and overall ductility. This provides improved formability and impact resistance for safety-related components made from the steel of this invention. Attached Figure Description

[0012] Figure 1 The annealing cycle of the present invention is illustrated schematically. Detailed Implementation

[0013] In a preferred embodiment, the strip or sheet has a composition (composition) consisting of the following alloying elements (in wt.%):

[0014]

[0015] The balance, excluding impurities, is Fe.

[0016] The composition does not include any coating applied to the strip or sheet.

[0017] The importance of each element and their interactions, as well as the limitations on the chemical composition of the claimed alloy, are briefly explained below. Throughout this specification, all percentages of the chemical composition of the steel are given in weight % (wt.%). Upper and lower limits for individual elements can be freely combined within the limits set forth in the claims. For all values ​​given in this application, the arithmetic precision of the numerical values ​​may be increased by one or two digits. Thus, a value given as, for example, 0.1% can also be expressed as 0.10 or 0.100%. The amount of microstructural components is given in volume % (vol.%).

[0018] C: 0.10-0.20%

[0019] Carbon (C) stabilizes austenite and is important for obtaining sufficient carbon content within the retained austenite phase. C is also important for achieving the desired strength level. Generally, it can be expected that tensile strength increases by approximately 100 MPa for every 0.1% increase in C. To achieve sufficient tensile strength, C should be at least 0.10%. The upper limit can be 0.20, 0.19, or 0.18%. The lower limit can be 0.10, 0.11, 0.12, 0.13, 0.14, or 0.15%. The preferred range is 0.13–0.18%.

[0020] Si: 0.3-0.9%

[0021] Si acts as a solid solution strengthening element and is important for ensuring the strength of thin steel strips. Si inhibits cementite precipitation and is essential for austenite stabilization. However, if the content is too high, too much silicon oxide will form on the strip surface, which can lead to cladding on the rolls in the continuous annealing line (CAL) and thus surface defects on the subsequently produced steel sheets. The upper limit can be 0.9, 0.8, 0.7, or 0.6%. The lower limit can be 0.3, 0.4, or 0.5%. The preferred range is 0.3–0.8%.

[0022] Mn: 1.4-3.0%

[0023] Manganese is a solid solution strengthening element, which works by reducing M s Temperature is used to stabilize austenite and prevent the formation of ferrite and pearlite during cooling. Furthermore, Mn lowers the austenite content. c3 Temperature is also important for austenite stability. At contents below 1.4%, it may be difficult to obtain the required amount of retained austenite and sufficient tensile strength. Furthermore, the required austenitizing temperature may be too high for conventional industrial annealing lines. Additionally, at lower contents, it may be difficult to avoid the formation of polygonal ferrite. If the amount of Mn is too high, problems related to segregation may occur, as Mn accumulates in the liquid phase and causes banding, leading to potentially degraded workability. Upper limits may be 3.0, 2.9, 2.8, 2.7, 2.6, 2.5, or 2.4%. Lower limits may be 1.4, 1.5, 1.6, 1.7, or 1.8%. The preferred range is 1.7–2.4%.

[0024] Al: 0.03-1.0%

[0025] The addition of Al can increase the carbon content in the retained austenite. Al can also be used as a deoxidizer. Like Si, Al is insoluble in cementite, thus delaying cementite formation during bainite formation and martensitic tempering. The addition of Al can further improve galvanizing and reduce susceptibility to embrittlement in liquid metals. However, M... s Temperature also increases with increasing Al content. A further drawback of Al is that it causes A... c3 The temperature increase. The upper limit can be 1.0, 0.9, 0.8, or 0.7%. The lower limit can be set to 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, or 0.1%. The preferred range is 0.03-0.8. If Al is only used for deoxidation, the upper limit can be 0.09, 0.08, 0.07, or 0.06%.

[0026] Si+Al: 0.5-1.5%

[0027] Si and Al inhibit cementite precipitation during bainite formation. Therefore, their combined content is preferably at least 0.5%. A preferred range is 0.6-1.3%.

[0028] Optional elements

[0029] Ti: ≤0.1%

[0030] Ti is commonly used in low-alloy steels to improve strength and toughness because it affects grain size by forming carbides, nitrides, or carbonitrides. In particular, Ti is a strong nitride forming agent and can be used to bind nitrogen in steel. However, this effect tends to saturate above 0.1%. Upper limits can be limited to 0.09, 0.07, 0.05, 0.03, 0.01, or 0.005%. According to the invention, it is not necessary to intentionally add Ti.

[0031] Nb: ≤0.1%

[0032] Nitrogen (Nb) is commonly used in low-alloy steels to improve strength and toughness due to its effect on grain size. Nb improves the strength-elongation balance by refining the matrix microstructure and retained austenite phase through the precipitation of NbC. The steel may contain ≤0.1% Nb. Upper limits may be limited to 0.09, 0.07, 0.05, 0.03, 0.01, or 0.005%. According to the invention, the intentional addition of Nb is not required.

[0033] V: ≤0.1%

[0034] V functions similarly to Nb because it contributes to precipitation hardening and grain refinement. Steel may contain ≤0.1% V. Upper limits may be limited to 0.09, 0.07, 0.05, 0.03, or 0.01%. According to the invention, V is not intentionally added.

[0035] Cr: ≤0.5%

[0036] Cr is effective in improving the strength of steel sheets. Cr is an element that forms ferrite and delays the formation of pearlite and bainite. A c3 Temperature and M sThe temperature decreases only slightly with increasing Cr content. Cr leads to an increase in the amount of stabilized retained austenite. Above 0.5%, it may impair the surface finish of the steel, and therefore, the amount of Cr is limited to 0.5%. The upper limit can be 0.50 or 0.40, 0.30, 0.20, 0.10 or 0.05%. The lower limit can be 0.01, 0.03, 0.05, 0.07, 0.10, 0.15, 0.20 or 0.25%. According to the invention, it is not necessary to intentionally add Cr.

[0037] B: ≤0.005%

[0038] Boron (B) inhibits ferrite formation and improves the weldability of steel sheets. For significant effects, at least 0.001% should be added. However, excessive B deteriorates machinability. B increases hardness but may come at the cost of reduced bendability and can make scrap recycling more difficult. According to the present invention, it is not necessary to intentionally add B.

[0039] Mo≤0.2%

[0040] Molybdenum is a powerful hardenability agent. It further enhances the benefits of NbC precipitates by reducing carbide coarsening kinetics. Therefore, steel can contain up to 0.2% Mo. Mo delays austenite decomposition and stabilizes retained austenite. Amounts exceeding 0.2% result in high costs. Upper limits can be limited to 0.2%, 0.1%, 0.05%, or 0.01%. Minimum amounts can be set to 0.001%, 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, or 0.05%. According to the invention, Mo does not need to be intentionally added.

[0041] impurities

[0042] The following impurities may be optionally restricted as disclosed below.

[0043] Ca: ≤0.05%

[0044] Ca can be used to modify non-metallic inclusions. The upper limit is 0.05%, and it can be set to 0.04, 0.03, 0.01, or 0.005%. According to the present invention, it is not necessary to intentionally add Ca.

[0045] Cu: ≤0.1%

[0046] Cu is an undesirable impurity element, which is limited to ≤0.1% by careful selection of the waste materials used. The upper limit is 0.1%, and it can be further limited to 0.05%.

[0047] Ni: ≤0.2%

[0048] Ni is also an undesirable impurity element, which is limited to ≤0.2% by carefully selecting the waste materials used. The upper limit is 0.2%, and it can be further limited to 0.1% or 0.05%.

[0049] Other impurity elements may be included in the steel in normal amounts. However, it is preferable to limit the amounts of P, S, As, Zr, and Sn to the following optional maximum contents:

[0050] P: ≤0.05, ≤0.04, ≤0.03, or ≤0.02%

[0051] S: ≤0.05, ≤0.03, ≤0.01, ≤0.005, or ≤0.001%

[0052] As: ≤0.020 or ≤0.010%

[0053] Zr: ≤0.010 or ≤0.006%

[0054] Sn: ≤0.030 or ≤0.015%

[0055] Oxygen and hydrogen can be further limited to

[0056] O: ≤0.001 or ≤0.0003%

[0057] H: ≤0.0050 or ≤0.0020%

[0058] It is also preferable to control the nitrogen content to the following range:

[0059] N: ≤0.015%, preferably 0.001-0.008%

[0060] Mechanical properties

[0061] Steel should meet the following conditions regarding tensile strength:

[0062]

[0063] Preferably, all of these requirements are met simultaneously.

[0064] TS, YS, and TE are examples of properties related to global extensibility. HER is a property related to local extensibility.

[0065] TS (Tensile Strength) (R) m The upper limit can be limited to 970, 960, 950, 940, 930, 910, 900, 890, 880, 870 or 860 MPa.

[0066] Rm R p0.2 The values, as well as the total elongation and / or ultimate elongation, are derived according to the industrial standard DIN EN ISO 6892-1, in which a sample with a gauge length of 80 mm is extracted in the longitudinal direction of the strip.

[0067] Hole expansion rate ( The hole enlargement test was performed according to ISO / WD 16630:2009 (E). In this test, a tapered punch with a 60° apex was forced into a hole with dimensions of 100 × 100 mm. 2 A 10mm diameter hole was punched in a steel sheet. The test was stopped once the first crack was identified, and the hole diameter was measured in two mutually orthogonal directions. The arithmetic mean was used for calculation.

[0068] Hole expansion rate ( (Calculated as a percentage) as follows:

[0069]

[0070] Where Do is the initial diameter of the hole (10mm) and Dh is the diameter of the hole after the test.

[0071] The thickness of the strip or sheet of the final product can be 0.1-4 mm, preferably 0.2-3 mm. Under non-slit conditions, the width of the strip or sheet can be 500-2000 mm, preferably 700-1750 mm.

[0072] microstructure

[0073] Microstructural components are expressed in volume % (vol.%) below.

[0074]

[0075] Each phase or combination of phases in the above list can be a margin for the microstructure.

[0076] Secondary tempered martensite is tempered martensite from the first quenching and partitioning (steps i and j) that is tempered again in the second partitioning step (step n). The lower limit of secondary tempered martensite can be 20, 25, 30, 35, 40, or 45 vol.%, and the upper limit can be 70, 65, 60, or 55 vol%. The preferred range is 40-60 vol.%.

[0077] Tempered martensite is martensite from the second quenching step that has been tempered in the second partitioning step. The lower limit for tempered martensite can be 0, 10, or 15 vol%. The upper limit can be 70, 60, 50, 40, or 30 vol%. The preferred range is 10-40 vol%.

[0078] Following the second quenching and partitioning (steps m and n), nascent martensite can form upon final cooling. A small amount of carbides may precipitate in the matrix. The upper limit for nascent martensite + carbides can be 10 or 5 vol%. The preferred range is 0-5 vol%.

[0079] The steel may contain bainite. The upper limit of bainite content can be 70, 60, 50, 40, 30, or 20 vol%. The lower limit can be 0, 5, or 10 vol%. The preferred range is 0-30 vol%.

[0080] The amount of tempered martensite + bainite is preferably 10-70 vol%, more preferably 20-40 vol%.

[0081] Retained austenite is a prerequisite for achieving the desired TRIP effect. The amount of retained austenite should be in the range of 5-25 vol%, preferably 10-20 vol%. Retained austenite has a dominant, uniform layered structure, which provides optimal mechanical stability, improved overall ductility, and improved local ductility for improving the TRIP effect.

[0082] The steel may optionally contain up to 10 vol% of other phases besides those described above, such as polygonal ferrite. Preferably, less than 5 vol% of other phases, and most preferably, the steel does not contain any other phases.

[0083] Microstructures (including the amounts of each phase) can be identified using a scanning electron microscope (SEM) at 2000x magnification. Preferably, this is done by cutting a sample from a steel plate and polishing a cross-section parallel to the rolling direction. The microstructure should be taken from a sample of a thickness of [missing information]. The surface can be etched to make the phases easier to identify.

[0084] Electron backscatter diffraction (EBSD) can be used for quantitative microstructure analysis in scanning electron microscopy. For example, secondary tempered martensite can be identified by local misorientation of 0° up to and including 0.5°, and tempered martensite can be identified by local misorientation of greater than 0.5° up to and including 1.2°.

[0085] The metallurgical reason for this difference stems from lower lattice distortion, as carbon diffuses further away from the body-centered tetragonal (bct) lattice of martensite during tempering to form carbides or partitions into the RA. Furthermore, dislocation annihilation during tempering results in a lower dislocation density, which reduces the local mismatch angle of the secondary tempered martensite.

[0086] However, the amount of retained austenite is preferably determined by the saturation magnetization method described in detail in Proc. Int. Conf. on TRIP-aided highstrength ferrous alloys (2002), Ghent, Belgium, pp. 61-64.

[0087] The improved properties of the retained austenite can be determined by one or more of the parameters described below.

[0088] Mechanical stability ) is a parameter describing the mechanical stability of retained austenite (RA). Influence Factors influencing the value include the chemical composition of austenite, primarily enriched by carbon, grain size (smaller grain size leads to more stable RA), and the morphology of RA (spherical RA is less stable than lath or acicular RA). For these reasons, the chemical composition of the steel and the heat treatment parameters are crucial.

[0089] The RA should have mechanical stability in the range of 10-35, preferably 15-25. (Above 35) The value indicates that the retained austenite (RA) has lower stability under mechanical loads. If the value is too high, the RA (Rapid Elongation) will have already transformed during elastic loading (stress-assisted) or under very low plastic strain and is therefore insufficient to increase the work hardening behavior of the steel and achieve high elongation. This invention aims for optimal stability of the RA. Within the suggested range... The value improves the stability of RA under mechanical loads and enhances its tolerance to RA decomposition. The upper limit can be 35, 30, 25, or 20. The lower limit can be 10, 12, 14, 15, or 16.

[0090] Mechanical stability This can be determined using interrupted tensile testing. The tensile specimen is deformed to a certain strain between the yield and necking of the specimen. The residual austenite content in the undeformed and deformed states is then determined.

[0091] The following relation applies (given by Ludwigson and Berger in J. Iron Steel Inst. 1969, Vol. 207, p. 63):

[0092]

[0093] ...initial retained austenite content

[0094] …residual austenite content after deformation

[0095] …real response

[0096] p… is a constant related to autocatalysis.

[0097] …indicators regarding the stability of retained austenite

[0098] Matsumura et al., in Scr. Metall. 1987, Vol. 21, p. 1301, proposed that in TRIP-assisted steel, p can be assumed to be 1. Therefore, The value can be derived from the combined results of interrupted tensile tests and retained austenite measurements. True strain is the natural logarithm of the ratio of the instantaneous gauge length to the original gauge length in the tensile test. The retained austenite content can be determined from saturation magnetization measurements. The initial retained austenite content ( It can be measured in the final heat-treated sample. The sample containing the retained austenite after deformation ( The gauge length of the deformed tensile specimen should be extracted. A sample with a gauge length of 80 mm should be extracted in the longitudinal direction of the strip.

[0099] Carbon content in retained austenite The following can be optionally satisfied (in wt.%):

[0100] 0.7-1.0

[0101] Within this range of carbon content in the retained austenite, an optimal combination of overall formability and local formability can be achieved. The preferred range is 0.8–0.95 wt%. The upper limit can be further limited to 0.90 wt%.

[0102] The carbon content in the retained austenite can be obtained by X-ray diffraction (XRD) measurements using the following equation. Lattice parameters obtained by reflection The calculations, as described in the equations in NH van Dijk, AM Butt, L. Zhao, J. Sietsma, SE Offerman, JP Wright, and S. van der Zwaag, *Thermal stability of retained austenite in TRIP steels studied by synchrotron X-ray diffraction during cooling*, Acta Materialia 53 (2005) 5439-5447, are as follows:

[0103]

[0104] in , and This refers to the content of carbon, manganese, and aluminum in austenite (in wt.%). Assuming the content... and It equals the nominal content of the alloy.

[0105] The amount of retained austenite (RA vol.%), the mechanical stability of austenite ( ) and the carbon content of retained austenite ( The following relationship should be satisfied:

[0106] ≥200, preferably 220-400

[0107] The average aspect ratio (AR) of the retained austenite (RA) and / or the average equivalent circle diameter (ECD) in μm can optionally satisfy the following relationship:

[0108] AR ≥2.0, preferably 2.03-2.30

[0109] ECD ≤0.57, preferably 0.45-0.55

[0110] The equivalent circle diameter (ECD) (in μm) and aspect ratio (AR) of the retained austenite (RA) can be determined by electron backscatter diffraction (EBSD). , where A is the measured area of ​​the grain. Aspect ratio = m / n, where m is the average length of the major axis of the grain and n is the average length of the minor axis of the grain. The measurement method is described in Li, M., Wilkinson, D. and Patchigolla, K. (2005) Comparison of Particle Size Distributions Measured Using Different Techniques. Particulate Science and Technology, 23, 265-284.

[0111] Further definition

[0112] Throughout the instruction manual, the temperature is given in degrees Celsius.

[0113] Ae1 and Ae3 represent the equilibrium transformation temperatures. Austenite is completely stable above Ae3 and partially unstable between Ae3 and Ae1. Ae1 and Ae3 are calculated using ThermoCalc 2022 TCFE 12.

[0114] M S Temperature usage can be found in S. Kaar, K. Steineder, R. Schneider, D. Krizan and C. Sommitsch: “New M S M in "formula for exact microstructural prediction of modern 3rd generation AHSS chemistries", Scr. Mater., Vol. 200, 2021, 113923 S Formula calculation.

[0115]

[0116] The M S The formula uses the content of each element as a percentage by weight.

[0117] M FThe formula originates from the Koistinen-Marburger equation found in (Koistinen, D. and Marburger, R: “A general equation prescribing the extent of the austenite-martensite transformation in pureiron-carbon alloys and plain carbon steels”, Acta Metall, 7, 1959, pp. 59-60):

[0118] ,

[0119] The fraction of martensite It is 0.95.

[0120] Production of cold-rolled strip

[0121] Cold-rolled steel strip can be produced through the following steps:

[0122] a) A conventional metallurgical billet is manufactured with the above composition by converter melting and secondary metallurgy.

[0123] b) The billet is hot-rolled into hot-rolled strip within the austenitic range. Preferably, this is done by reheating the billet to a temperature between 1000°C and 1280°C. Preferably, the billet is rolled entirely within the austenitic range, wherein the hot-rolling finish temperature is greater than or equal to 850°C, thereby obtaining hot-rolled steel strip.

[0124] c) Thereafter, the hot-rolled strip can be wound at a winding temperature in the range of 400-700°C.

[0125] d) Optionally, annealing is performed at a temperature ranging from 500 to 950°C. Preferably, batch annealing is performed at 500 to 700°C for a duration of 5 to 30 hours. Alternatively, the strip may be continuously annealed at a temperature ranging from 650 to 950°C for 10 to 200 seconds.

[0126] e) Optionally, the wound strip may be subjected to a descaling process (e.g., pickling) before and / or after intermittent annealing.

[0127] f) Subsequently, cold-rolled annealed steel strip is produced at a reduction rate of 20-90%, preferably about 50-70%.

[0128] The steps a)-f) described above for manufacturing cold-rolled strip are examples of how cold-rolled strip can be manufactured. This invention can be applied to cold-rolled strip produced by other known steps.

[0129] According to the present invention, the cold-rolled strip is subjected to the double annealing process disclosed in steps a) to p). Figure 1 The thermal cycle of the double annealing process is shown.

[0130] The first annealing cycle described in steps g) to k) is a quenching and partitioning (Q&P) process, in which the steel is annealed and then quenched to M. s -20℃ and M F The temperature is between [temperature range], then the fractionation is carried out at a temperature higher than the quenching temperature, and finally cooled to room temperature. The second annealing cycle is described in steps l) to p).

[0131] First annealing cycle:

[0132] g) Supplying cold-rolled steel strip to a continuous annealing line, the steel strip having the composition described above.

[0133] h) Heat the strip to a first annealing temperature (Tan1) between 800°C and 1000°C at a rate of 1-20°C / second (HR1), and homogenize it for 10-300 seconds (tan1). Preferably, the first annealing temperature (Tan1) is higher than Ae3.

[0134] i) Cool the strip at a rate of 10-100°C / second (CR1) to M F and (M) S The first quenching temperature (TQ1) is between -20°C and M. The lower limit can be further restricted to M. F And the highest value selected from 150, 160, 170, and 180°C. The upper limit can be further restricted to M. S -30, M S -40, M S -50, M S -60, M S -70, M S -80, M S -90 or M S -100℃.

[0135] j) The cooled strip is heated to a first partitioning temperature (Toa1) within the range of the first quenching temperature (TQ1) + 10°C to 500°C at a rate of 1-100°C / second (HR2), and the strip is partitioned for 20-1000 seconds (toa1). Preferably, the first partitioning temperature (Toa1) is higher than M. SThe upper limit can be limited to 500, 480, 450, 430 or 410℃. The lower limit can be limited to 260, 280, 300, 320, 340, 360 or 380℃.

[0136] k) Cool the strip to a temperature below 50°C at a rate of 1-50°C / second (CR2), preferably to room temperature.

[0137] After the first annealing cycle, the steel matrix consists of tempered martensite with a relatively high amount of carbides and RA. Prior to the second annealing, the higher amount of carbides and RA ensures more nucleation sites for austenite formation. This results in a higher amount of RA in the second annealing cycle, exhibiting optimal stability against strain-induced martensitic transformation (SIMT) and a fine microstructure with a layered morphology that improves both overall and local formability. This combination of overall and local formability surpasses all known dual-annealing concepts.

[0138] The second annealing cycle following the first annealing cycle (steps g to k):

[0139] l) The strip is heated to a second annealing temperature (Tan2) between 700°C and 900°C at a rate of 1-20°C / second (HR3) and homogenized for 10-300 seconds (tan2). Preferably, the second annealing temperature (Tan2) is within the critical range, i.e., between Ae1 and Ae3. However, it is permissible for the second annealing temperature (Tan2) to be higher than Ae3.

[0140] m) Cool the strip to a second quenching temperature (TQ2) in the range of 150-500℃ at a rate of 10-100℃ / s (CR3). The second quenching temperature (TQ2) can be lower than M. S Preferred to be lower than (M) S -20)℃, and must be higher than M F .

[0141] The upper limit can be limited to 500, 450, 400, 350, 300 or 250℃. The lower limit can be limited to 150, 170, 200, 220, 240, 260, 280 or 300℃.

[0142] n) The strip is divided for 20-1000 seconds (toa2) at a second partitioning temperature (Toa2) within the range of the second quenching temperature (TQ2) to 500°C. The upper limit can be limited to 500, 480, 450, or 430°C. The lower limit can be limited to 150, 200, 250, 300, or 350°C. The heating rate (HR4) to the second partitioning temperature (Toa1) can be in the range of 1-100°C / second. In the case of isothermal tempering, there is obviously no heating rate from the second quenching temperature (TQ2) to the second partitioning temperature (Toa1), that is, in this case, the heating rate (HR4) is 0°C / second.

[0143] o) Cool the strip to a temperature below 50°C at a rate of 1-50°C / second (CR4), preferably to room temperature.

[0144] p) Optionally, a sheet is manufactured from the strip.

[0145] Optional coatings

[0146] The steel sheet or strip may optionally be coated and contain a zinc or zinc alloy coating. The coating may be applied, for example, by the following methods:

[0147] - Electroplated zinc (EG), including electroplating.

[0148] - Physical vapor deposition (PVD).

[0149] - Hot-dip galvanizing (HDG) in a hot-dip galvanizing line, wherein the strip is immersed in a molten zinc bath at the end of the final batching (step n). The hot-dip galvanizing line can be the same as a continuous annealing line with added hot-dip coating.

[0150] - Zinc annealing (GA) in a galvanizing annealing line is similar to a hot-dip galvanizing line, but with an added annealing step after hot-dip coating. That is, it is processed in the same way as a continuous annealing line, but includes zinc annealing (step n) at the end of the final fractionation. Zinc annealing is a combination of zinc plating and annealing at approximately 480-560°C to promote a higher degree of Fe in the ZnFe coating.

[0151] Zinc alloy coatings may contain, by weight percent:

[0152] Mg 0.1-10

[0153] Al 0.1-10

[0154] Optionally, one or more of the following:

[0155] Bi, Pb, Sn, Sb, Si, Ti, Ca, Mn, La, Ce, Cr, Ni, and Zr, in total amounts ranging from 0.01 to 1.0.

[0156] The balance consists of Zn and impurities.

[0157] The coating that has been galvanized and annealed may contain 5-20 wt.% diffused Fe.

[0158] Other coating compositions known in the art can be applied.

[0159] Example

[0160] Two alloys, L1 and L2, are produced by conventional metallurgical processes including converter smelting and secondary metallurgy. The composition of the alloys (elements in [wt%]) is shown in Table 1, with further elements present only as impurities and below the minimum levels specified in this specification. M S M F The measured values ​​(in °C) for Ae1 and Ae3 are also shown in Table 1.

[0161] Unless otherwise stated, the parameter values ​​throughout the embodiments are determined by the methods previously given in the specification.

[0162] Table 1

[0163]

[0164] Alloys L1 and L2 are continuously cast and cut into billets. The billets are then reheated and hot-rolled in the austenitic range to a thickness of approximately 2.8 mm. The hot-rolling finish temperature is approximately 900°C. Subsequently, hot-rolled steel strip is wound at a coiling temperature of 630°C. The wound hot-rolled strip is pickled and intermittently annealed at approximately 624°C for 10 hours to reduce the tensile strength of the hot-rolled strip and thus reduce the cold-rolling force. The strip is then cold-rolled in a five-stand cold rolling mill to a final thickness of approximately 1.4 mm.

[0165] All steels undergo two final annealing cycles in the continuous annealing line, with Table 2a showing the process values ​​for the first annealing cycle and Table 2b showing the process values ​​for the second annealing cycle. The annealing cycles are schematically illustrated in... Figure 1 In this context, the reference sample is denoted by Rn, where n = 0, 1, 2, 3, and the sample of the present invention is denoted by Sn, where n = 1…5.

[0166]

[0167]

[0168] Except for sample R0, all samples underwent double annealing. Sample R0 was single annealed. After the first annealing, reference samples R1-R3 were quenched to room temperature without any fractionation before the second annealing. After the first annealing, samples S1-S5 of the present invention were quenched to below M. S -20℃ but higher than M F The temperature. Subsequently, before the second annealing, samples S1-S5 of the present invention are dispensed at a temperature higher than the quenching temperature. After the first annealing, the reference sample R0 is quenched to a temperature lower than M. S -20℃ but higher than M F The temperature is then adjusted, and subsequently distributed at a temperature higher than the quenching temperature.

[0169] After the second annealing, the sample is quenched and then partitioned at a temperature higher than the quenching temperature, or it is quenched and held isothermally after quenching.

[0170] The mechanical properties and details of the retained austenite are shown in Table 3. The steels of the present invention (S1-S5) have similar tensile strengths compared to reference steels (R1-R3) of the same composition. However, the total elongation and porosity of the steels of the present invention are greater than those of the reference steels of the same composition. Therefore, the product of the tensile strength, total elongation, and porosity of the samples of the present invention is significantly greater than that of the reference samples. Based on these findings, the standards for the steel, for example… and The results clearly show that no reference sample met the requirements. or .

[0171]

[0172] The microstructures of samples S3 and S5 after the second annealing cycle were examined. The microstructures comprised a matrix with a layered morphology and including secondary tempered martensite, tempered martensite, bainite, and a large amount of RA. The amount of RA was determined to be 12% and 14% vol%, respectively. The results are presented in Table 4.

[0173]

[0174] The average aspect ratio (AR) and average equivalent circle diameter (ECD) of the residual austenite (RA) of the reference sample R2 were determined and compared with the sample S5 of the present invention.

[0175] The results are shown in Table 5.

[0176]

[0177] The following conclusions can be drawn from the results shown in Table 5.

[0178] - For the samples of this invention, the amount of RA is relatively high.

[0179] - For the sample of this invention, the carbon content of RA Lower.

[0180] - For the sample of this invention, the ECD of RA is smaller.

[0181] - For the samples of this invention, RA has a higher AR.

[0182] - Only samples of this invention meet the standards. .

[0183] Despite a smaller ECD and a higher AR, the lower C content in the RA compared to the reference material results in lower but optimal stability of the RA for strain-induced martensitic transformation (SIMT) in the samples of this invention. This leads to better utilization of the TRIP effect and thus better overall formability. Furthermore, the lower C content in the RA ensures a lower hardness difference between the matrix and the RA, which also improves local formability in the case of the samples of this invention.

Claims

1. High-strength steel strip or sheet, possessing: a) Composition consisting of the following elements, in wt.%: The balance, excluding impurities, is Fe; b) Tensile strength (R) m 780-970MPa Among them, tensile strength (R) m The sample is obtained according to the industrial standard DIN EN ISO 6892-1, in which a sample with a gauge length of 80 mm is extracted in the longitudinal direction of the strip. c) Contains the following microstructures, in vol.%: Residual austenite 5-25 The amount of retained austenite was measured by means of saturation magnetization, which is described in detail in Proc. Int.Conf. on TRIP-aided high strength ferrous alloys (2002), Ghent, Belgium, pp. 61-64, and the other phases were determined by means of scanning electron microscopy (SEM) at 2000x magnification. d) Where the retained austenite satisfies: Mechanical stability 10-35, As defined by Ludwigson and Berger in J. Iron Steel Inst. 1969, Vol. 207, 10, p. 63, where p=1: ...initial retained austenite content …residual austenite content after deformation …genuine response; Carbon content of retained austenite (in wt.%): 0.7-1.0, in Determined by the following formula: in and It is the content of manganese and aluminum in austenite (in wt.%), and, where it is assumed that... and The content is equal to the nominal content, and is obtained by X-ray diffraction (XRD) measurement using the following equation. The lattice parameter a is obtained by reflection. γ The equation described is in NH van Dijk, AM Butt, L. Zhao, J. Sietsma, SE Offerman, JP Wright and S. van der Zwaag, Thermalstability of retained austenite in TRIP steels studied by synchrotron X-ray diffraction during cooling, Acta Materialia 53 (2005) 5439-5447; and ≥200, RA refers to the amount of retained austenite. The microstructures described therein meet the following requirements in vol.% terms: Secondary tempered martensite 20-70 Tempered martensite 0-70 Bainite 0-70 New martensite + carbides 0-5 Residual austenite (RA) 5-25 Bainite + Tempered Martensite 10-70 Other phases 0-10, The secondary tempered martensite can be identified as having a local mismatch angle of 0° up to and including 0.5° by using electron backscatter diffraction (EBSD) in scanning electron microscopy (SEM), and the tempered martensite can be identified as having a local mismatch angle of greater than 0.5° up to and including 1.2°.

2. The steel strip or sheet according to claim 1, wherein the microstructure satisfies at least one of the following requirements in vol.% terms: , The secondary tempered martensite can be identified as having a local mismatch angle of 0° up to and including 0.5° by using electron backscatter diffraction (EBSD) in scanning electron microscopy (SEM), and the tempered martensite can be identified as having a local mismatch angle of greater than 0.5° up to and including 1.2°.

3. The steel strip or sheet according to any one of claims 1-2, wherein it satisfies one or more of the following mechanical properties: , Among them, yield strength (R) p0.2 ) and total elongation (A 80 According to industrial standard DIN EN ISO 6892-1, a sample with a gauge length of 80 mm is extracted in the longitudinal direction of the strip, and Among them, the hole expansion ratio ( The results were determined by the enlargement test according to ISO / WD 16630:2009 (E).

4. The steel strip or sheet according to any one of claims 1-2, wherein, Meets one or more of the following mechanical properties: , Among them, yield strength (R) p0.2 ) and total elongation (A 80 According to industrial standard DIN EN ISO 6892-1, a sample with a gauge length of 80 mm is extracted in the longitudinal direction of the strip, and Among them, the hole expansion ratio ( The results were determined by the enlargement test according to ISO / WD 16630:2009 (E).

5. The steel strip or sheet according to any one of claims 1-2, wherein the retained austenite satisfies one or more of the following: , The aspect ratio (AR) and equivalent circle diameter (ECD) of the retained austenite (RA) were determined by means of electron backscatter diffraction (EBSD) according to the method described on page 11 of the specification.

6. The high-strength steel strip or sheet according to any one of claims 1-2, having a composition consisting of the following alloying elements (in wt.%): The balance, excluding impurities, is Fe.

7. The steel strip or sheet according to claim 1, wherein the microstructure satisfies all of the following requirements in vol.% terms: , The secondary tempered martensite can be identified as having a local mismatch angle of 0° up to and including 0.5° by using electron backscatter diffraction (EBSD) in scanning electron microscopy (SEM), and the tempered martensite can be identified as having a local mismatch angle of greater than 0.5° up to and including 1.2°.

8. The steel strip or sheet according to claim 3, wherein YS represents the yield strength (R). p0.2 The pressure is 500-700 MPa.

9. The steel strip or sheet according to claim 3, wherein the HER has a hole expansion ratio (λ) of 50-90%.

10. The steel strip or sheet according to claim 3, wherein TE represents the total elongation (A) 80 The percentage is 20-30%.

11. The steel strip or sheet according to claim 3, wherein TS*TE*HER / 100 is 12000-20000 MPa.

12. A method for producing high-strength steel strip or sheet according to any one of claims 1-11, comprising: g) Providing cold-rolled steel having the composition defined in item a) of any one of claims 1-11: h) Heat the strip to a first annealing temperature (Tan1) between 800°C and 1000°C at a rate of 1-20°C / second (HR1), and homogenize for 10-300 seconds (tan1). i) Cool the strip at a rate of 10-100°C / second (CR1) to M F To (M) S The first quenching temperature (TQ1) is between -20℃ and 20℃. j) The cooled strip is heated to a first partitioning temperature (Toa1) within the range of the first quenching temperature (TQ1) + 10°C to 500°C at a rate of 1-100°C / second (HR2), and the strip is partitioned for 20-1000 seconds (toa1). k) Cool the strip to a temperature below 50°C at a rate of 1-50°C / second (CR2). l) Heat the strip to a second annealing temperature (Tan2) between 700°C and 900°C at a rate of 1-20°C / second (HR3) and homogenize for 10-300 seconds (tan2). m) The strip is cooled to a second quenching temperature (TQ2) in the range of 150-500°C at a rate of 10-100°C / second (CR3). n) The strip is divided for 20-1000 seconds (toa2) at a second distribution temperature (Toa2) within the range of the second quenching temperature (TQ2) to 500°C. o) Cool the strip to a temperature below 50°C. p) Optionally, a sheet is manufactured from the strip.

Citation Information

Patent Citations

  • High-strength dual-phase steel sheet superior in elongation and formability for extension flange

    JP2004238679A

  • High-strength cold-rolled steel sheet and method of manufacturing the same

    US20160177414A1

  • High strength steel products and annealing processes for making the same

    US20170327924A1

  • High-strength steel sheet and production method therefor

    US20190203316A1

  • Cold rolled and heat treated steel sheet and a method of manufacturing thereof

    US20200354823A1